Psychological Aspects of the Treatment of Patients with Disorders of Sex Development - Sandberg, David E.; Gardner, Melissa; Cohen-Kettenis, Peggy T. (Seminars in Reproductive Medicine, 2012)
Research on the psychological development of persons with Disorders of Sex Development (DSD) has focused on understanding the influence of atypical sex hormone exposure during steroid-sensitive periods of prenatal brain development on the process of psychosexual differentiation (i.e., gender identity, gender role, and sexual orientation). In contrast, analysis of clinical management strategies has focused on gender assignment and the desirability and timing of genital surgery.This review focuses on the psychological issues that confront clinicians managing the care of persons born with DSD and their families. Particular attention is paid to processes and factors that potentially mediate or moderate psychosocial and psychosexual outcomes within and across developmental stages.
Keywords: disorders of sex development; DSD; psychosocial; psychosexual; gender identity; gender role; sexual orientation